Characterization of immunoglobulin E-binding proteins (IgE) of scomberomorus commerson lacepede - Rosmilah Misnan,; Shahnaz Murad,; Masita Arip,; Noormalin Abdullah,; Jamaludin Mohamed, (penerbit ukm, 2005)
The objective of this study was to determine the Immunoglobulin E-binding proteins (IgE) and major allergens of Scomberomorus commerson Lacepede(Narrow-barred Spanish mackerel). Allergen extracts were obtained from uncooked and cooked fish by homogenization in phosphate-buffered saline followed by continuous extraction at 4oC or on ice. Protein profiles and IgEbinding patterns were then detected by means of sodium dodecyl polyacrylamidegel electrophoresis (SDS-PAGE) and immunoblotting using sera from patients sensitized to the fish. SDS-PAGE of the uncooked fish extracts revealed 26 protein bands in the range of about 11 to >175 kD, while the cooked extracts produced fewer protein bands. Immunoblotting demonstrated 17 IgE-binding bands, ranging in molecular weight from 11 to 151 kD. Two components with molecular weight of about ~50 and 42 kD showed the highest frequency of IgE-binding (62.2 and 51.4% respectively) and were identified as the major allergens of this fish allergy. Other IgE-binding proteins including a protein at ~12 kD which was equivalent in size to parvalbumin were identified as the minor allergens.